The sovereign trickster death and laughter in the age of Duterte - Rafael, Vicente L. (Ateneo de Manila University Press, 2022)
"In The Sovereign Trickster Vicente L. Rafael offers a prismatic view of the age of Rodrigo Duterte in the contemporary Philippines. Framing Duterte as a trickster figure who boasts, jokes, terrorizes, plays the victim, and instills terror, Rafael weaves together topics ranging from the drug war, policing, and extra-judicial killings to neoliberal citizenship, intimacy, and photojournalism. He is less concerned with defining Duterte as a fascist, populist, war lord, and traditional politician than he is with examining what Duterte does: how he rules, the rhetoric of his humor, his use of obscenity to stoke fear, and his projection of masculinity and misogyny. Locating his rise within the context of counterinsurgency, neoliberalism, and the history of electoral violence, while drawing on Foucault's biopower and Mbembe's necropolitics, Rafael outlines how Duterte weaponizes death to control life. By diagnosing the symptoms of the authoritarian imaginary as it circulates in the Philippines, Rafael provides a complex account of Duterte's regime and the social conditions that allow him to enjoy continued support"--